PENGARUH PERSEPSI KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA DAN PRESTASI KERJA GURU SMK PGRI SE KABUPATEN BOJONEGORO - jurnalmap map; Rahma Hidayatul Husna; Nugroho Mardi Wibowo; Soenarmi ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This study aims to describe and know effect both simultanously and partialythe conditions of perception variable compensation, work environment, work motivation and job performance of teachers SMK PGRI Bojonegoro. The population in this study were all teachers at SMK PGRI Bojonegoro as many as 45 people. The sampling technique used purposive sampling that takes most members of the population being sampled with certain characteristics in accordance with the intent and purpose of the study. In this study, the sample used is not permanent teachers (GTT) SMK PGRI in Bojonegoro. The method used is descriptive statistics and path analysis (path analysis). Perception of compensation, work environment and work motivation simultaneously no significant direct impact on the performance of teachers. Perception of compensation have no direct impact significantly on the performance of teachers. Work environment significant direct effect on the performance of teachers. Work motivation have a significant effect on the performance of teachers. Perception of compensation and working environment simultaneously no significant effect on work motivation of teachers. Perception compensation significant effect on work motivation of teachers. The work environment has no significant effect on work motivation of teachers SMK PGRI Bojonegoro. Keywords: compensation, work environment, motivation, job performance